2007
DOI: 10.1118/1.2794225
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the cine‐CT based 4D‐CT imaging

Abstract: An improved 4D-CT utility has been developed on the GE LightSpeed multislice CT (MSCT) and Discovery PET/CT scanners, which have the cine CT scan capability. Two new features have been added in this 4D-CT over the commercial Advantage 4D-CT from GE. One feature was a new tool for disabling parts of the respiratory signal with irregular respiration and improving the accuracy of phase determination for the respiratory signal from the Varian real-time positioning and monitoring (RPM) system before sorting of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 16 publications
(12 reference statements)
0
93
0
Order By: Relevance
“…The images are obtained from superposition of the maximum and minimum intensity projection images of the low dose cine thoracic CT images obtained without contrast for oncological purposes. 1 The radiation dose for the low dose cine CT was about two times radiation dose of a regular helical CT. coronary imaging, a recent 18 F-NaF coronary imaging study utilized only one cardiac phase with 1/4th of the counts compared to the full PET acquisition. 19 This approach, however, results in reduced count statistics with higher image noise.…”
Section: Coronary Pet Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The images are obtained from superposition of the maximum and minimum intensity projection images of the low dose cine thoracic CT images obtained without contrast for oncological purposes. 1 The radiation dose for the low dose cine CT was about two times radiation dose of a regular helical CT. coronary imaging, a recent 18 F-NaF coronary imaging study utilized only one cardiac phase with 1/4th of the counts compared to the full PET acquisition. 19 This approach, however, results in reduced count statistics with higher image noise.…”
Section: Coronary Pet Imagingmentioning
confidence: 99%
“…Respiratory motion can cause the heart to move more than 1 cm in natural tidal breathing, as shown in Figure 1 on low-dose cine-CT imaging during free breathing and superposition of the maximum and minimum intensity projections of the cine-CT images over one respiratory cycle. 1 In fact, if we consider the heart as a large tissue mass above the diaphragm, we could consider findings with regards to the magnitude of 'tumor' motion extensively reported in radiation treatment literature, as well as technologies deployed in radiation therapy to cope with respiratory motion. The seminal paper by Seppenwoolde et al 2 using fluoroscopy to measure respiratory motion clearly demonstrated that most of the respiratory motion is in the craniocaudal direction, which was later shown as well in PET.…”
Section: Degradation Of Cardiac Pet Images By Motionmentioning
confidence: 99%
“…[77][78][79] However, it is not clear whether the setup of 4-dimensional CT imaging primarily for the assessment of tumor motion is ideal for obtaining average CT when most PET/CT scanners are in nuclear medicine and are without the respiratory monitoring device needed for 4-dimensional CT. A practical approach is to acquire average CT without a respiratory monitoring device to improve quantification of the PET data. 51,80 The additional radiation dose for average CT can be less than 1 mSv, and the additional scan time is less than one minute and will not impact the overall scan time of a PET/CT procedure. Selection of optimum parameters for acquiring average CT with cine CT or low-pitch helical CT has been reported.…”
Section: Average Ct Of Less Than 1 Msv Reduces Misregistrationmentioning
confidence: 99%
“…A 4D image set is then reconstructed by viewing the 3D images in sequence for each image bin. The current acquisition and sorting methods led to significant motion artifacts 4 , 6 (artifacts in one study measured <4mm in 90% of scans (5) ). The occurrence of artifacts is mainly caused by inaccurate determination of the respiratory phase (4) .…”
Section: Introductionmentioning
confidence: 99%
“…The current acquisition and sorting methods led to significant motion artifacts 4 , 6 (artifacts in one study measured <4mm in 90% of scans (5) ). The occurrence of artifacts is mainly caused by inaccurate determination of the respiratory phase (4) . These artifacts manifest themselves in the CT images as undefined and/or irregular boundaries, consequently degrading image clarity and causing errors in patient contouring and dose calculation 7 , 8 …”
Section: Introductionmentioning
confidence: 99%